Molecularly imprinted polymers in biological applications - El-Schich, Zahra; Zhang, Yuecheng; Feith, Marek; Beyer, Sarah; Sternbæk, Louise; Ohlsson, Lars; Stollenwerk, Maria; Wingren, Anette Gjörloff (BioTechniques, 2020)
Molecularly imprinted polymers (MIPs) are currently widely used and further developed for biological applications. The MIP synthesis procedure is a key process, and a wide variety of protocols exist. The templates that are used for imprinting vary from the smallest glycosylated glycan structures or even amino acids to whole proteins or bacteria. The low cost, quick preparation, stability and reproducibility have been highlighted as advantages of MIPs. The biological applications utilizing MIPs discussed here include enzyme-linked assays, sensors, in vivo applications, drug delivery, cancer diagnostics and more. Indeed, there are numerous examples of how MIPs can be used as recognition elements similar to natural antibodies.
Keywords: Neoplasms; nádory; Animals; polymerizace; lékové transportní systémy; zvířata; biologické markery; Polymerization; Biomarkers; Drug Delivery Systems; Molecularly Imprinted Polymers; molekulárně imprintované polymery